Inhibition of formyl peptide receptors improves the outcome in a mouse model of Alzheimer disease - Nicole Schröder; Anja Schaffrath; Josua A. Welter; Tim Putzka; Angelika Griep; Patrick Ziegler; Elisa Brandt; Sebastian Samer; Michael T. Heneka; Hannes Kaddatz; Jiangshan Zhan; Eugenia Kipp; et al. (Journal of Neuroinflammation, 2020)
Abstract Background An important hallmark of Alzheimer’s disease (AD) is the increase of Aβ1-42 burden and its accumulation to senile plaques, leading the reactive gliosis and neurodegeneration. The modulation of glia cell function represents an attractive therapeutic strategy, but is currently limited by an incomplete understanding of its relevance for AD. The chemotactic G-protein coupled formyl peptide receptor (FPR), which is known to modulate Aβ1-42 uptake and signal transduction, might be one candidate molecule regulating glia function in AD. Here, we investigate whether the modulation of FPR exerts beneficial effects in an AD preclinical model. Methods To address this question, APP/PS1 double-transgenic AD mice were treated for 20 weeks with either the pro-inflammatory FPR agonist fMLF, the FPR1/2 antagonist Boc2 or the anti-inflammatory FPR2 agonist Ac2-26. Spatial learning and memory were evaluated using a Morris water maze test. Immunohistological staining, gene expression studies, and flow cytometry analyses were performed to study neuronal loss, gliosis, and Aß-load in the hippocampus and cortex, respectively. Results FPR antagonism by Boc2-treatment significantly improved spatial memory performance, reduced neuronal pathology, induced the expression of homeostatic growth factors, and ameliorated microglia, but not astrocyte, reactivity. Furthermore, the elevated levels of amyloid plaques in the hippocampus were reduced by Boc2-treatment, presumably by an induction of amyloid degradation. Conclusions We suggest that the modulation of FPR signaling cascades might be considered as a promising therapeutic approach for alleviating the cognitive deficits associated with early AD. Additional studies are now needed to address the downstream effectors as well as the safety profile of Boc2.